An architecture for Grid-enabled distributed simulation. (8th June 2009) - Jiang, Ming; Theodoropoulos, Georgios; Anane, Rachid
The application of distributed simulation techniques to ever more complex problems calls for more computational power. The emergence of the Grid provides an opportunity to address this challenge and thus make advances in the modelling and analysis of large-scale systems by harnessing the power of many computers. These requirements are met by the design and development of frameworks that support the integration of appropriate Distributed Simulation Kernels (DSK) and Grid middleware. This paper presents a framework and a prototype implementation for specifying and executing distributed simulations over the Grid. The framework incorporates a well established DSK with the Globus middleware.